ORDO : Jahrbuch für die Ordnung von Wirtschaft und Gesellschaft (De Gruyter Oldenbourg, 1948)
ORDO is a forum for the discussion of fundamental concepts in institutional and regulatory economics and their application to real-life national and international problems. ORDO is the only academic journal in the German-speaking world that explicitly specializes in the interplay between economic, legal, political, and social organizational systems.